Use of public transport by stroke survivors with persistent disability - Kjell Asplund; Sari Wallin; Fredrik Jonsson (Scandinavian Journal of Disability Research, 2012)
Use of public transport (bus, train, air, ship) by persons disabled after stroke is an expression of autonomy and facilitates social interactions. Based on Riks-Stroke, the Swedish stroke register, 882 persons with persistent, moderate or severe physical disability (mean age 71 years) responded to a questionnaire 12–28 months after stroke. A minority of the respondents had travelled by bus (21%), train (9%), air (14%) or ship (12%) during the last year. Barriers perceived by persons that had abstained from travelling were dominated by physical constraints, but there were also frequent cognitive constraints. Fear of travelling was not perceived as a major constraint. The majority of persons who had actually used public transport did not report any negative experiences. Air and ship journeys were generally perceived as somewhat less troublesome than journeys by bus or train. Thus, public transport is used infrequently in people moderately or severely disabled after stroke. Anticipated cognitive constraints contribute importantly to non-use of public transport. Disabled stroke survivors who have not used public transport may overestimate the actual barriers to use of public transport.